Imago Dei di Era Digital: Peran Manusia sebagai Pembawa Misi Allah dalam Dunia Modern - Lalala, Evalin (PT. Giat Konseling Nusantara, 2025)
The article explores in depth the meaning of Imago Dei (the image of God) within the context of the digital era and its implication for the role of humans as bearers of God's mission (Missio Dei) amid the changes of the times. The concept of Imago Dei, rooted in the creation narrative of Genesis 1:2-27, affirms that human beings possess value, diginty, and the capacity to reflect God's character throught relasionships, morality, and responsibility for creation. however, in the digital age characterized by cultural transformation, technological dependence, and the dominance of social media the understanding of human identity as the image of God faces serious challenges. the virtual world often constructs new standards of existence and meaning that diverge from Christian values, such as superficial self-presentation, the culture of digital validation, and fragile virtual relationships. as a response to these dynamics, the church and christian communities are called to be activetly and wisely present in the digital realm by upholding the values of love, truth, justice, and integrity. this includes engaging in ethical communicaion, disseminating, trustworthy information, and utilizing social media as a medium for evangelism and spitirual character formation. thus, digitalization should not be viewed solely as a threat, but also as a strategic mission opportunity to manifest Imago Dei and carry out Missio Dei in contemporary context. this article aims to contribute both theologically and practically to the discourse on navigating unavoidable technological developments, and to serve as a reflective call for Christians to live out their faith in ways that are both relevant and impactful in the digital age.